Fermented Feed for Laying Hens: Effects on Egg Quality and the Number of Enteric Pathogenic Bacteria Present - Amantsura, Daimeera Anja Lulu; Retnaningrum, Endah (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Eggs are one of the most common food sources for human consumption because they are common, easy to obtain, and nutritious. Eggs contain abundant vitamins and minerals that the human body needs, are a good source of protein and fat and are rich in choline. Despite its high nutritional value, eggs are also one of the leading causes of food poisoning and foodborne diseases in various countries. This is due to contamination in eggs by pathogenic bacteria such as Salmonella, Shigella, Escherichia coli, and Campylobacter bacteria. Fermented chicken feed contains natural probiotics added to the feed, which improves gut health, better absorption of nutrients, inhibits the growth of pathogenic bacteria, enhances the immune response in chickens. This study is conducted to distinguish the diffrence in quality of eggs that can be physically observed in chicken eggs fed with fermented feed compared to chicken eggs fed regular feed, as well as to compare the number of total bacteria and enteric pathogenic bacteria contained in the contents of chicken eggs that includes Escherichia coli and Salmonella spp bacteria. The methods used in this research include observing egg quality comparisons, calculating and comparing the total number of bacteria, and testing for the presence of enteric pathogenic bacteria Escherichia coli and Salmonella, spp. using the plate count method. The resulting data was processed using the one-way ANOVA method with a confidence level of 95%. The results of this research show higher egg quality in fermented fed eggs which is characterized by the color of the yolk which tends to be darker yellow to orange and thicker egg shells. The total bacteria count showed that the bacteria was significantly lower in eggs from chickens fed fermented feed. Tests for the number of enteric bacteria showed positive results for E. coli in 1 out of 10 egg content samples from chicken fed with fermented feed, and positive results for E. coli in 2 out of 10 egg samples from chicken fed with regular feed, while test results for Salmonella spp. showed negative results in all samples.